High Rates of Methicillin-Resistant Staphylococcus aureus Colonization of Domesticated Swine of Kabale District – Southwestern Uganda - Andrew, Baguma; Kagirita, Atek Atwiine; Tonny, Owalla; Joel, Bazira (Journal of Advances in Microbiology, 2018)
Background: S. aureus is a commensal mammalian pathogen which can establish itself as part of the skin flora. However, can eventually cause infections and invasive diseases in both hospital and community settings. Livestock-associated Methicillin-resistant S. aureus remains a major concern to public health. This study investigated the rates of methicillin resistance S. aureus (MRSA) colonization and respective antibiotic resistance profiles in domestic pigs in Kabale District - South Western Uganda. Method: This was a cross-sectional study conducted between June 2016 and February 2017 in which nasal swabs from 585 pigs from 147 homesteads were collected and cultured using standard microbial techniques to isolate S. aureus and phenotypically screen for MRSA using Cefoxitin disc. MecA polymerase chain reaction (PCR) was used to confirm MRSA. Antimicrobial susceptibility testing was performed using the Kirby Bauer technique to determine antimicrobial susceptibility pattern among MRSA towards to the commonly used antibiotics in the region. Result: From the five hundred and eighty-five (585) pigs, 172 (29.4%) were MRSA. There was high antibiotic resistance among MRSA isolates was observed against Sulfamethoxazole – trimethoprim was 170(99%), Erythromycin; 154(89%), Ciprofloxacin 124(72%), Clindamycin; 121(70), Tetracycline; 121(70%), Gentamycin; 84(49%), Rifampicin; 40(23%); Cefipime; 40(23%) and Vancomycin; 03(2%). Conclusion: The observed high rate of MRSA colonization among domestic pigs is of a significant public health concern in Kabale region. A greater number of MRSA isolates were highly resistant to commonly used antibiotics.
Keywords: MRSA; Swine; Uganda